Satanism as Reflected in Alan Walker’s Selected Song Lyrics - Insani, Ina; Budiwati, Tri Rina (NOTION: Journal of Linguistics, Literature, and Culture, 2021)
This research aims to identify and describe the discourse structures and analyze the representation of Satanism found in the lyrics of the selected songs of Alan Walker. The researcher used the Critical Discourse Analysis approach by Teun van Dijk to determine Satanism in these songs. Three elements are used in this analysis, namely the discourse structure, social cognition, and social context. This research found that there are elements of discourse structure, whether explaining the micro-structure, superstructure, or macro-structure, always address Satanism’s idea. The social cognition aspect found that the social condition influences Satanism's notion in the Alan Walker songs in Norway, where Alan Walker lives open to Satanism. It can be seen from the analysis of model and memory. The analysis of model in Alan Walker's song can be influenced by the social conditions around him. The analysis of memory shows how his personal experience affects the songs he produces. The last aspect in this research is the social context which analyse the power and access to know the idea of Satanism in the songs. The analysis of power found that Satanism has a strong dominance in Norway, as seen from several works such as books, films, and music with the theme of Satanism. Then, the analysis of access found that the satanic people managed to control several media in Norway.